Perilaku Komunikasi Nonvebal: Dosen Terbaik dan Dosen Terburuk - Nurmida Catherine Sitompul (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2018)
This study aims to determine whether lecturers perceived as the best or worst based on their nonverbal communication behaviors are influenced by students’ cultural backgrounds. Employing an ex post facto design, the independent variable was the type of lecturers’ nonverbal communication behavior, categorized into the Best Lecturer and the Worst Lecturer. The dependent variable was students’ perceptions of lecturers’ nonverbal communication behavior, with students’ ethnic backgrounds (Javanese, East Nusa Tenggara, and Madurese) serving as the moderating variable. The participants were students from four study programs. Data were collected using the Nonverbal Immediacy Measure (NIM) questionnaire, with 203 valid responses analyzed. A mean difference test was used to examine perceptual differences, and the Kruskal–Wallis One-Way ANOVA was employed to test the hypotheses. The results indicate that there is no significant difference in students’ perceptions of lecturers’ nonverbal communication behavior between the best and worst lecturers across different cultural backgrounds.